Virtual Screening of Human Serum Albumin Mutants to Optimize the Search for its Forms that Increase Affinity to Amyloid-Β Peptide - Deryusheva Evgenia; Machulin Andrey; Litus Ekaterina (BIO Web of Conferences, 2023)
A promising approach to the treatment of Alzheimer's disease (AD) is the removal of amyloid-β peptide (Aβ) from the patient's central nervous system by acting on human serum albumin (HSA). HSA carries 90% of Aβ in blood serum and 40-90% of Aβ in the cerebrospinal fluid (CNS). In this work, virtual screening of all possible mutant forms of HSA based on the data of the I-Mutant service made it possible to predict changes in HSA stability and identify the most “sensitive” regions of its polypeptide chain to substitutions. The data obtained will be used to optimize the search for HSA forms with increased affinity to Aβ, as well as to study the mechanisms underlying the modulating effects of HSA ligands on its interaction with Aβ, which can become the basis for the development of new approaches to therapy and prevention of AD.